ORC guide to research project management. - University of the Philippines (Diliman). Office of Research Coordination (Quezon City U.P. Office of Research Coordination, 1995)
This guide aims to make research project management more efficient. The topics covered in this guide are qualifications and duties of the personnel, procedure in disbursement of funds, policies in project monitoring, and requirements in the accomplishment of the final report. Definitions of terms are included in this guide. It also includes appendices containing guidelines and principles on creative work.
Keywords: Research -- Management -- Handbooks, manuals, etc